2015
DOI: 10.1080/20445911.2015.1055274
|View full text |Cite
|
Sign up to set email alerts
|

Rapid makes risky: Time pressure increases risk seeking in decisions from experience

Abstract: Time pressure is a common constraint on many real-world decisions, such as those made by traders placing orders in the stock market, bidders in an auction, or gamblers at a casino. Many of these situations also involve elements of risk or uncertainty. Previous research has mostly found that time pressure leads to more risky choices. These previous studies, however, have examined decisions made from probabilities that were explicitly described, rather than learned through experienced outcomes. Here we tested ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 58 publications
5
50
0
Order By: Relevance
“…In general, behavior is observed to be more heuristic. Similar findings are obtained by Madan et al (2015), who state that under higher time pressure subjects choose risky options more often, independent of the outcome value. Additionally, they find time pressure moderately increasing risk seeking in decisions from experience.…”
supporting
confidence: 75%
“…In general, behavior is observed to be more heuristic. Similar findings are obtained by Madan et al (2015), who state that under higher time pressure subjects choose risky options more often, independent of the outcome value. Additionally, they find time pressure moderately increasing risk seeking in decisions from experience.…”
supporting
confidence: 75%
“…Similarly, in vignette studies, time pressure led participants to search for possible safety measures providing them with more control in the risky option ('risk defusing operators'), eventually making them choose it more often (Huber and Kunz, 2007). More recently, Madan et al (2015) reported that time pressure induced a modest shift towards risk seeking when information about outcome probabilities was conveyed through experience rather than description.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Each door/option appeared equally often on either side of the screen. Performance of lower than 60% on catch trials in either decisions from description or experience across the whole experiment was used as an exclusion criterion, following established protocol from previous experiments (Ludvig et al, 2014a(Ludvig et al, , 2014bLudvig & Spetch, 2011;Madan et al, 2014Madan et al, , 2015. Data from 18 of the 256 participants were thus excluded.…”
Section: Methodsmentioning
confidence: 99%